Cyclodextrin-functionalized thiophene-based copolymers and their guest-host recognition behaviour - Soheila Bahmanjah. (2010)
To construct super-molecular systems which recognize the structure of guest molecules, 3-bromo-alkylthiophene monomers bearing side chains (n = 6 & 8) have been polymerized into corresponding copolymers using the GRIM method. These copolymers are quantitatively and rapidly converted into functionalized polymers under mild conditions by post polymerization reactions with 6^A-amino-6^A-alpha-deoxy-cyclodextrin and 6^A-amino-6^A-beta-deoxy-cyclodextrin.These polythiophene derivatives exhibit a highly conjugated form in the solid state at room temperature and their molecular recognition behaviour has been investigated. Cyclic voltammetry shows strong affinity and selectivity of these polymers for a wide range of organic guests such as 3, 4-dihydroxyphenylalanine (DOPA), 1, 4-Dihydroxybenzene, 1, 4-Dihydroxynaphthalene, (S/R) Camphor, (S/R) Carvone, (S/R) Menthol and (S/R) Mandelic acid. Presence of these molecules in electrolytic media displayed a dramatic influence over the electrochemical properties of these polythiophene derivatives. An advantage of this design is that the sensory mechanism functions via reversible molecular recognition events, thereby allowing a completely reversible response such that in the absence of analyte, the sensory material returns back into its original unperturbed state. Details of polymer synthesis and the electrochemical behaviour are discussed.